US a narrative history Vol. 1 to 1877 - Davidson, James West. (New York McGraw-Hill, 2009)
The first civilizations of North America; Old worlds, new worlds(1400-1600); Colonization and conflict in the South (1600-1750); Colonization and conflict in the North (1600-1700)...
Includes bibliographical references and index.
Keywords: United States -- Textbooks -- History; Hoa Kỳ (Nước Mỹ); Lịch sử nước Mĩ